2019
DOI: 10.3390/agronomy10010015
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Responses of Major Fruit Crops to Fertilization in China: A Meta-Analysis

Abstract: With increasing application of nitrogen (N), phosphorus (P), and potassium (K) fertilizers, especially in China’s fruit crops, the agronomic responses of fruit crops to fertilization may be reduced with time. Thus, the quantification of these responses would be useful for establishing nutrient recommendation and fertilizer management for fruit crops. Here, a meta-analysis including 552 paired data for agronomic response and 1283 sets for amounts of optimal fertilization from 293 field studies in China were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
1
16
1
1
Order By: Relevance
“…Similar results were found in studies with Phaseolus vulgaris L. and Vigna radiata, where the yield was reduced by 73 to 313% when lime was not applied to acid soils [42,43]. Therefore, [38] indicated that the application of lime in an acidic soil is necessary to significantly increase the yield of the crops by 13 to 67%.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were found in studies with Phaseolus vulgaris L. and Vigna radiata, where the yield was reduced by 73 to 313% when lime was not applied to acid soils [42,43]. Therefore, [38] indicated that the application of lime in an acidic soil is necessary to significantly increase the yield of the crops by 13 to 67%.…”
Section: Discussionsupporting
confidence: 78%
“…The highest yield obtained in Palora is possibly due to the variation of abiotic factors such as climatic conditions such as temperature and solar radiation [37,38]. Palora can reach until 80 light hours monthly and temperatures between 18 and 29 • C and rarely less than 16 • C. In this environment, plants showed early flowering and fruiting, factors influenced by the heliophany.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable tools able to quantify nutrient demand will significantly enhance nutrient use efficiency by minimizing overapplication errors. Li et al [17] conducted a meta-analysis of nearly 300 nutrient-response studies of fruit crops conducted over four decades. While the results showed increased yields over time, they also showed slightly reduced agronomic efficiency and partial factor productivity for NPK due to increased soil nutrient supply.…”
Section: Nutrient Rates-recommendationsmentioning
confidence: 99%
“…The results showed that 62375.18 MJ/ha energy was consumed by orange orchards and 77501.17 MJ/ha by mandarin orchards. A meta-analysis of agronomic response of major fruit crops (citrus, apple, water melon, banana, grape, kiwi, jujube, mango, papaya, lychee, apple, apricot, pomegranate etc) to fertilization in China by Li et al (2019a) showed that the yield response to N, P, or K fertilizer were 7.6, 5.2, or 5.9 tons/ha, indicating relative yield of 78.08%, 82.9%, or 82.4%, respectively, with higher relative yield for deciduous fruit trees compared to evergreen fruit trees. A rationale nutrient managements, therefore, crucial for balancing yield and environmental concerns in countries like China, India, and other countries where fertilizers are often over-used.…”
Section: Introductionmentioning
confidence: 99%